2018
DOI: 10.1063/1.5050143
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of butterfly (Lepidoptera: Papilionoidea) along altitudinal gradients at Gunung Ledang National Park, Johor, Malaysia

Abstract: Abstract. Gunung Ledang, or previously known as Mount Ophir is the highest highland in south Peninsular Malaysia, in the state of Johor. Along with its elevations, climate, and vegetation vary. These influence the distribution of flora and fauna such as butterfly. The objectives of this study were (i) to document the diversity of butterfly along elevational gradients and (ii) to analyze species diversity patterns based on faunistic aspect. To determine spatial distribution, this study was conducted at three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This study focused on the pattern of butterfly diversity and assemblages along the different elevations in the rainforest of Borneo. Butterflies are sensitive towards subtle changes in their environment which make them an excellent bioindicator to assess environmental changes (Ismail et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study focused on the pattern of butterfly diversity and assemblages along the different elevations in the rainforest of Borneo. Butterflies are sensitive towards subtle changes in their environment which make them an excellent bioindicator to assess environmental changes (Ismail et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the `humped-shape' pattern of altitudinal diversity was reported and discussed in several studies (Guo et al, 2013). The environment at a higher elevation with low temperature, high humidity, cloudy and less sunlight, less plant species and compact forest canopy could affect the butterfly abundance (Ismail et al, 2018). In contrast, a study conducted at Gunung Ledang in Peninsular Malaysia found that the number of butterfly species and abundance were high at an altitude of 400m, but showed a sharp decrease with increasing altitude (Ismail et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly observed pattern for insect communities is a reduction in richness and abundance at higher elevations, with greater diversity in low or mid zones (FERNANDES et al, 2016;PIRES et al, 2020), and such trend also applies to Lepidoptera. Studies carried out in different environments demonstrated that low elevations host a greater diversity of Lepidoptera, with more uniform species distribution (SPARROW et al, 1994;ISMAIL et al, 2018). Other investigations found greater diversity in mid-elevation zones, where temperature and rainfall levels were within the optimal range for butterfly survival (STEFANESCU et al, 2004;ILLÁN et al, 2010;ABRAHAMCZYK et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical mountains, moreover, are regarded as hotspots of biodiversity and endemism (Chen et al, 2009;Merckx et al, 2015), and Malaysia is among the biodiversity hotspots in South East Asia. There are number of studies on species diversity patterns along elevational gradients such as land snails (Liew et al, 2010), leaf litter ants (Brühl et al, 1999), litter-dwelling ants (Yusah et al, 2012), black fly (Ya'cob et al, 2016) and butterflies (Ismail et al, 2018;Abdullah and Musthafa, 2019). Diversity studies of beetles have been fairly well covered by the scientific community, but they focused little on the diversity change across elevations in the montane ecosystems.…”
Section: Introductionmentioning
confidence: 99%